The Effect of Financial Performance and Exchange Rate on Stock Return - Hidayat, Muhammad Rasyid; Nursyirwan, Vivi Iswanti (Universitas Pamulang, 2023)
This study aims to determine how the current ratio and the exchange rate can affect stock returns. This study uses an associative quantitative approach. The population in this study are companies listed on the Indonesia Stock Exchange in the category of manufacturing companies in the consumer goods industry sector, food and beverage sub-sector taken from 2016-2020 as many as 32 companies. The sampling technique in this research is purposive sampling. The results of this study state that the current ratio does not affect stock returns, but the exchange rate affects stock returns.